2007
DOI: 10.1073/pnas.0607123104
|View full text |Cite
|
Sign up to set email alerts
|

Replication is required for the RecA localization response to DNA damage in Bacillus subtilis

Abstract: In both prokaryotes and eukaryotes, proteins involved in DNA repair often organize into multicomponent complexes that can be visualized as foci in living cells. We used a RecA-GFP fusion to examine the subcellular cues that direct RecA-GFP to assemble as foci in response to DNA damage. We used two different methods to inhibit initiation of DNA replication and determined that DNA replication is required for the cell to establish RecA-GFP foci after exposure to DNA-damaging agents. Furthermore, use of endonuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 55 publications
11
92
1
Order By: Relevance
“…In E. coli and Bacillus subtilis, RecA-GFP fusion proteins have been visualized as foci in response to DNA damage and replication of damaged DNA. 33,34) The PpRecA2-GFP foci may form in response to cpDNA damage, which might be caused in the course of the procedure for protoplast preparation and subsequent transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli and Bacillus subtilis, RecA-GFP fusion proteins have been visualized as foci in response to DNA damage and replication of damaged DNA. 33,34) The PpRecA2-GFP foci may form in response to cpDNA damage, which might be caused in the course of the procedure for protoplast preparation and subsequent transformation.…”
Section: Discussionmentioning
confidence: 99%
“…By coupling homologous recombination with DNA replication status, a cell may ensure that this requirement is met. A study using a partially functional recAgfp fusion allele integrated at the native recA locus as the only source of RecA activity in the cell showed that ongoing DNA replication was necessary for RecA-GFP to form foci in response to single-strand gaps or an I-SceI-induced DSB in vivo (387). In this study, a DSB was generated and RecA-GFP failed to organize into a focus when DNA replication initiation was blocked (387).…”
Section: Reca Recruitment Loading and Coupling To Dna Synthesismentioning
confidence: 99%
“…This could aid in vivo in the repair of DNA damage such as interstrand cross-links at replication forks, as already suggested. However, the overall roles of these proteins in repair and genome maintenance are still unclear (387). SbcE (YhaN) was recently identified as an SMC family protein in B. subtilis which has a role in DNA repair (189).…”
Section: Potential Roles For Other Smc-like Proteins In Dsb Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Resuspend the cells in up to 2 mL of S750 medium from the LB agar plate with single colonies or the light confluent cells to obtain an inoculum. 4. Add enough S750 medium-cell inoculum to the Erlenmeyer flask containing 10 mL S750 medium for a culture with an initial optical density measured at 600 nm (OD600) of~0.08 to 0.1.…”
Section: Protocolmentioning
confidence: 99%